Delinquency and default in usa student debt as a proportional response to unemployment and average debt per borrower - José Alberto Fuinhas; Victor Ferreira Moutinho; Estefano Silva (Economies, 2019)
We research the response of the proportion of student borrowers with ninety or more days of delinquency or in default to variables such as unemployment and the average debt per borrower after the financial crisis of 2007-2008, in the United States, using panel data of 50 states from 2008 to 2015. The proportion of borrowers with delinquency or default was modelled as a function of unemployment, the average debt per borrower, consumer sentiment, and financial stress, using a logit and probit binomial model. The specification tests support that no relevant variable was omitted. Unemployment and the average debt per borrower are statistically significant and contribute to increasing delinquency or default in the 50 states of the panel sample. The results also reveal a differential impact of unemployment among the four regions considered by the US Census Bureau.
Keywords: I23; G21; C23; 330; average debt per borrower; consumer sentiment; financial stress; fractional probit; panel data; student loan default; unemployment